2012
DOI: 10.5539/ells.v2n1p85
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Functional Linguistics in Exposing Gender Bias in Iranian High School English Textbooks

Abstract: The purpose of the present study is to find out whether Iranian high school English textbooks are sexist textbooks which discriminate between male and female students based on their sex. Halliday's systemic-functional linguistic theory was used as an innovative framework to language gender bias studies. To this end, four English textbooks currently taught in the Iranian high schools were chosen as a sample of this study. The linguistics analysis revealed that there were more males in the Theme and Rheme positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
6
0
8
Order By: Relevance
“…The roles of females and their realistic contributions to the society are not well represented in the textbooks because there is an imbalance in gender representation. Although this study showed improvement to some areas of the textbooks when compared with the results of the previous researches (Feiz Mohammadpour, 1999;Mousavi, 2012a and2012b) which examined the same textbooks (1999 edition), there are still further for improvements in order to avoid negative impacts of Hidden Curriculum and to provide an equal learning opportunity for all students. According to HC theory as the textbooks present students with texts which emphasize on males importance and more This indoctrination of a false belief can affect students massively on their decision making about their desired study field or a favored job (Vahdatinejad & Bahiyah 2017a).…”
Section: Discussionmentioning
confidence: 47%
“…The roles of females and their realistic contributions to the society are not well represented in the textbooks because there is an imbalance in gender representation. Although this study showed improvement to some areas of the textbooks when compared with the results of the previous researches (Feiz Mohammadpour, 1999;Mousavi, 2012a and2012b) which examined the same textbooks (1999 edition), there are still further for improvements in order to avoid negative impacts of Hidden Curriculum and to provide an equal learning opportunity for all students. According to HC theory as the textbooks present students with texts which emphasize on males importance and more This indoctrination of a false belief can affect students massively on their decision making about their desired study field or a favored job (Vahdatinejad & Bahiyah 2017a).…”
Section: Discussionmentioning
confidence: 47%
“…Dalam mengevaluasi buku teks terutama untuk buku teks bahasa Inggris, hal yang harus dievaluasi tidak hanya berfokus pada topik berbasis bahasa seperti tenses, kata sifat, kata kerja, tetapi juga harus memperhatikan aspek sosial. Dari banyak sumber yang disintesis dari sepuluh aspek evaluasi buku teks, salah satunya adalah masalah gender dalam pendidikan, seperti memeriksa beberapa implikasi gender dalam bahan dan interaksi kelas (Sunderland, 2000), meneliti efek stereotip gender dalam sastra anak-anak (Bowker, 1996), meneliti representasi laki-laki dan perempuan dalam buku teks (Sari, 2011), mencari tahu perbedaan antara laki-laki dan perempuan dalam buku teks bahasa Inggris (Gharbavi & Ahmad Mousavi, 2012) Analisis buku teks dari perspektif gender adalah penting. Karena buku teks adalah sebagai sumber belajar terutama dalam konteks di mana penilaian umumnya sangat terfokus pada menghafal, buku teks dapat dengan mudah menjadi alat untuk mempromosikan bias, termasuk bias gender atau mengekspos stereotip gender (Loan et al, 2010).…”
Section: Pendahuluanunclassified
“…Penelitian tentang representasi gender dalam buku pelajaran bahasa Inggris telah muncul sejak tahun 1970-an (Hartman & Judd, 1978;Lakoff, 1973) sejalan dengan kesadaran kesetaraan gender dalam pendidikan. Setelah itu, studi gender menjadi semakin populer di kalangan peneliti baik dari negara-negara barat (Bowker, 1996;Clark, 1990;Hellinger, 1980;Kingston & Lovelace, 1977;Porreca, 1984) atau negaranegara Asia (Bakar et al, 2015;Ebadi & Seidi, 2015;Esmaeili & Arabmofrad, 2015;Gebregeorgis, 2016;Gharbavi & Ahmad Mousavi, 2012;Jannati, 2015;Jean & Yuit, 2012;Lee, 2014Lee, , 2019Salami & Ghajarieh, 2016;Toçi & Aliu, 2013;Yasin et al, 2012) karena mereka percaya bahwa isu-isu gender dapat memengaruhi proses belajar mengajar dalam praktik kelas melalui penggunaan buku teks.…”
Section: Pendahuluanunclassified
“…Vettorel and Lopriore claim that in the 1990s: "studies on EFL textbooks saw a shift from content to linguistic analysis (2013, p. 140). Gharbavi (2012) and Hameed (2014) targeted vocabulary and structure as language aspects in their linguistic analyses. i.e.…”
Section: Review Of the Literature Gender Representation Areas In Englmentioning
confidence: 99%